Current situation on ectoparasitosis in dogs in Moscow - S. B. Devyatyarova (Российский паразитологический журнал, 2023)
The purpose of the research is the study of the current situation on ectoparasite infections in dogs in Moscow considering the season of the year.Materials and methods. The current situation on ectoparasitosis in dogs in Moscow was studied on the basis of the VNIIP – FSC VIEV and OOO GLOBALVET CLINIC (Moscow) in 2020–2022. Ninety-four dogs were examined in different seasons of the year. When examining the animals, attention was paid to pelage and skin damage. The history was taken with the animal sex, age, and pelage and skin state taken into account; the ears were examined; the pelage was combed out using a magnifying glass; ear contents were microscopically examined; and scrapings of the superficial and deep layers of the skin were made. The results were statistically processed using Microsoft Excel.Results and discussion. The infection of the dogs with Demodex canis was the highest possible in the autumn-winter period (7.4%), and in spring and summer it decreased to 5.3 and 4.2%, respectively. Ixodes ricinus ticks were only found on the skin and pelage of the dogs (18%) in the warm season. No significant difference was observed in the infection of the dogs with Otodectes cynotis, Sarcoptes canis and Cheyletiella jascuri in different seasons of the year. The seasonal dynamics of the infection of the dogs with different species of insects varied. Fleas were found in winter in 6.4% of the dogs, and in spring and summer in 8.5% and 10.6% of the dogs, respectively. The infection of the dogs with lice was 3.2% in winter, 4.2% in spring, 5.3% in summer and 6.4% in autumn. The maximum infection of dogs with lice was observed in summer (4.2%), and it decreased in winter to 2.1%.